2012
DOI: 10.1073/pnas.1200125109
|View full text |Cite
|
Sign up to set email alerts
|

Relative luminance and binocular disparity preferences are correlated in macaque primary visual cortex, matching natural scene statistics

Abstract: Humans excel at inferring information about 3D scenes from their 2D images projected on the retinas, using a wide range of depth cues. One example of such inference is the tendency for observers to perceive lighter image regions as closer. This psychophysical behavior could have an ecological basis because nearer regions tend to be lighter in natural 3D scenes. Here, we show that an analogous association exists between the relative luminance and binocular disparity preferences of neurons in macaque primary vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
45
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 52 publications
9
45
0
Order By: Relevance
“…Previous neurophysiological work has identified cells in primary visual cortex (V1) that are jointly tuned for both relative luminance (increments and decrements) and depth (via binocular disparities). This previous work reported systematic biases in the joint tuning properties of these cells but did not directly compare these biases to the statistical distributions of luminance and depth in natural scenes (Samonds et al, 2012). We sought to compare these neurophysiology data with the information avail- able in natural scenes to determine whether these cell tunings indeed reflect an efficient encoding of the available depth information (Ganguli and Simoncelli, 2010).…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Previous neurophysiological work has identified cells in primary visual cortex (V1) that are jointly tuned for both relative luminance (increments and decrements) and depth (via binocular disparities). This previous work reported systematic biases in the joint tuning properties of these cells but did not directly compare these biases to the statistical distributions of luminance and depth in natural scenes (Samonds et al, 2012). We sought to compare these neurophysiology data with the information avail- able in natural scenes to determine whether these cell tunings indeed reflect an efficient encoding of the available depth information (Ganguli and Simoncelli, 2010).…”
Section: Resultsmentioning
confidence: 98%
“…In motion processing, recent work has suggested that ON/OFF segregation is maintained and used to exploit higher-order patterns that are created by motion in natural scenes (Clark et al, 2014). In depth processing, as discussed in the Introduction, neurons involved in stereo-depth computations are jointly tuned for luminance with an overall correlation consistent with natural scenes (Samonds et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations